The Search of miRNA Related to Invasive Growth of Nonfunctioning Gonadotropic Pituitary Tumors - Joanna Boresowicz; Paulina Kober; Natalia Rusetska; Maria Maksymowicz; Agnieszka Paziewska; Michalina Dąbrowska; Natalia Zeber-Lubecka; Jacek Kunicki; Wiesław Bonicki; Jerzy Ostrowski; Janusz A. Siedlecki; Mateusz Bujko (International Journal of Endocrinology)
Purpose. Nonfunctioning gonadotropic pituitary neuroendocrine tumors (PitNETs) are among the most frequent neoplasms of pituitary gland. Although PitNETs are commonly considered benign, a notable part of patients suffer from tumor recurrence after treatment. Invasive growth of pituitary tumor is among the most important prognostic factors. Since molecular features of invasiveness are of potential clinical usefulness, this study was aimed to verify whether invasive and noninvasive nonfunctioning gonadotropic PitNETs differ in the miRNA expression profile and whether the differences could provide a possible molecular classifier. Methods. miRNA profiles were determined in 20 patients (11 invasive and 9 noninvasive tumors) using next-generation sequencing. The expression of selected miRNAs was assessed in the independent cohort of 80 patients with qRT-PCR. Results. When miRNA profiles of invasive and noninvasive tumors were compared, 29 miRNAs were found differentially expressed. Hsa-miR-184, hsa-miR-181a-2-3p, hsa-miR-93-3p, hsa-miR-574-5p, hsa-miR-185-5p, and hsa-miR-3200-5p showed a potential clinical value according to ROC curve analysis. Unfortunately, differential expression of only hsa-miR-185-5p was confirmed in the validation cohort, with AUG at 0.654. Conclusion. Differences in miRNAs expression profiles in invasive and noninvasive gonadotropic PitNETs are slight and the level of miRNA expression seems not to be applicable as useful classifier of tumor invasiveness.